Semiconductor subsidies and WTO rules - Gary Clyde Hufbauer (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2024)
Subsidies to the semiconductor industry have been massive ever since chips were created in the 1950s. Yet, semiconductor subsidies have never been challenged in the GATT or WTO, and rarely in bilateral commercial relations. Reasons suggest a permanent vacuum of subsidy discipline for this and kindred industries.
Keywords: 330